1995
DOI: 10.1159/000184587
|View full text |Cite
|
Sign up to set email alerts
|

Low Adrenal Androgens in Men with HIV Infection and the Acquired Immunodeficiency Syndrome

Abstract: Using gas chromatography and mass spectrometry we have studied the ratios of steroid metabolites and 24-hour urinary steroid excretion rates in 37 men of whom 14 where positive for the human immunodeficiency virus (HIV; group A), while 9 had acquired immunodeficiency syndrome (AIDS; group B). Controls were sick non-AIDS patients admitted to an intensive care unit (ICU) and healthy volunteers. In groups A and B and the ICU controls, there was a reduction in the excretion of adrenal androgen metabolites and a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…33,[39][40][41] In addition to the low production of testosterone by the Leydig cells, shunting from androgen production to cortisol secretion by the adrenal glands has been demonstrated. 33,35,37,42 Opportunistic infections were also frequently encountered in the pre-HAART era; cases of toxoplasmosis, cytomegalovirus, Mycobacterium avium intracellulare, Cryptococcus neoformans, and Histoplasma capsulatum causing primary (testicular) and/or secondary (hypothalamus/pituitary) hypogonadism were reported. [43][44][45][46][47][48][49][50] HIV-associated malignancies such as Kaposi's sarcoma and lymphoma were also implicated.…”
Section: Pathogenesis Of Hypogonadismmentioning
confidence: 99%
“…33,[39][40][41] In addition to the low production of testosterone by the Leydig cells, shunting from androgen production to cortisol secretion by the adrenal glands has been demonstrated. 33,35,37,42 Opportunistic infections were also frequently encountered in the pre-HAART era; cases of toxoplasmosis, cytomegalovirus, Mycobacterium avium intracellulare, Cryptococcus neoformans, and Histoplasma capsulatum causing primary (testicular) and/or secondary (hypothalamus/pituitary) hypogonadism were reported. [43][44][45][46][47][48][49][50] HIV-associated malignancies such as Kaposi's sarcoma and lymphoma were also implicated.…”
Section: Pathogenesis Of Hypogonadismmentioning
confidence: 99%
“…HIV infection can also result in decreased adrenal androgen secretion, with shunting of adrenal androgen metabolism to at Rutgers University Libraries/Technical Services on April 10, 2015 http://cid.oxfordjournals.org/ Downloaded from cortisol secretion [20], similar to that observed among patients with systemic illness who are hospitalized in an intensive care unit [21].…”
Section: Etiology Of Androgen Deficiency In Hiv-infected Menmentioning
confidence: 69%
“…Hallmarks of progressive HIV disease include symptoms such as persistent fatigue, loss of muscle mass, loss of sexual function, and many other testosterone driven disorders. SULT2B1 is a key gene in androgen synthesis pathways, and investigators have identified gonadal and adrenal androgen deficiencies in people living with HIV disease (Croxson et al, 1989; Honour, Schneider, & Miller, 1995). Testosterone-replacement therapies have improved fatigue in men living with HIV (Rabkin, Wagner, McElhiney, Rabkin, & Lin, 2004).…”
Section: Resultsmentioning
confidence: 99%